Knowledge, attitude, and practice of medical and health sciences students in IIUM Kuantan regarding human papilloma virus vaccination - Mohammed Ahmed, Abdulkareem; Elsayed, Tarek Mohamed Ali; Fata Nahas, Abdul Rahman; Jamshed, Shazia Qasim (International Journal of Pharmaceutical Sciences and Research, 2018)
Introduction: Human Papilloma Virus (HPV) is the major causal agent for the fourth most frequent cancer in women which is cervical cancer. HPV vaccine is already available as the primary prophylactic method for cervical cancer. The objective of this study was to assess the level of knowledge, attitude and practice regarding HPV and its vaccination among medical and health sciences students in the International Islamic University Malaysia (IIUM). Materials and Methods: This study was conducted from November until December 2017. Pretested and validated questionnaire was distributed among third-year students from the faculties of medicine, dentistry, pharmacy, and allied health sciences. Results: The results showed that the level of knowledge was good for medicine and dentistry students while poor for pharmacy and allied health sciences students. Medicine students showed the highest level of knowledge compared to other faculties (p=0.000016). The majority of students had a positive attitude towards HPV vaccination. A small percentage of students were fully vaccinated (13.65%, 37) with no significant difference between different faculties. Conclusion: In conclusion, the levels of knowledge and attitude of the respondents were high and positive, respectively. More awareness, healthcare programs, and campaigns should be run at the campus.